IMPLEMENTATION OF GOOD GOVERNANCE IN VILLAGE DEVELOPMENT PLANNING IN OGAN ILIR REGENCY - Athaya, Naurah; Mardianto, Mardianto; Rafinzar, Rahmat (Universitas Negeri Yogyakarta, 2024)
This study discusses the implementation of good governance in village development planning meetings (Musrenbangdes) in Pulau Semambu based on the principles of good governance according to Sedarmayanti, namely accountability, transparency, participation, and rule of law. The research method used is descriptive qualitative research. Data collection techniques were used through observation, interviews, documentation, and literature study. The results showed that the implementation of good governance in the Village Development Planning Meeting in Semambu Pulau did not fulfill all the principles of good governance (1) In terms of accountability, the government had not yet formed an organizing team and a Musrenbangdes guiding team ; (2) In terms of transparency, there is still minimal outreach by the government; (3) In terms of participation, there has been a decrease in the level of community participation; (4) In terms of the rule of law, lack of knowledge of organizers regarding the guidelines and rules. The advice given in this study is to provide training and guidance related to the implementation procedures of Musrenbangdes, as well as involve academics and other facilitators to provide assistance and provide understanding regarding the ideal concept of organizing Musrenbangdes by the guidelines. The government should also provide a web-based information system to disseminate information.